2014
DOI: 10.1177/2319510x14539743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Consumer Decision-making Styles of Youth in Shopping Malls

Abstract: Purpose The main purpose of this research article is to identify decision-making styles of Indian youth using consumer style inventory. Design/methodology/approach A survey was done on Indian youth to understand decision-making styles in shopping malls. A total sample of 223 youth was taken from two different universities of Punjab. Findings One of the key finding that consumer scale inventory (CSI) is not confirmed to Indian youth who like to go to shopping malls for recreation, and best value deals. Youth ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…family and friends) and impersonal sources (e.g. media channels) of information (Bedi, 2014). Based on the description above, the third hypothesis proposed in this study: H3: Consumer Characteristic has significant influence on ecologically conscious consumer behavior.…”
Section: Environmental Concernmentioning
confidence: 90%
See 1 more Smart Citation
“…family and friends) and impersonal sources (e.g. media channels) of information (Bedi, 2014). Based on the description above, the third hypothesis proposed in this study: H3: Consumer Characteristic has significant influence on ecologically conscious consumer behavior.…”
Section: Environmental Concernmentioning
confidence: 90%
“…The key focus of the present research is fewer environmental concerned variables, mostly because they have been undertaken in a developing country (Pradeep Kautish & Ganesh Dash, 2017). Based on the description above, the second proposed hypothesis in this study is: H2: Environmental Concern has significant influence on ecologically conscious consumer behavior Consumer Characteristic Bedi (2014) has shown that the environmental consciousness consumers can have effects on their purchasing decisions, although the other moderating factors may also influence their purchase decisions. The findings confirm that there is a hierarchy of attitudinal value in the green buying context.…”
Section: Environmental Concernmentioning
confidence: 99%